2020
DOI: 10.34172/apb.2021.026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Medicinal Plants and Flavonoids on Parkinson's Disease, a Review on Basic and Clinical Evidences

Abstract: Parkinson’s disease (PD) is a neurodegenerative disorder which is characterized by typical symptoms including gradual progressive muscle rigidity, tremor and loss of motor skills. Although there is no definitive cure for PD, the extract of some medicinal plants and their ingredients have been suggested to relieve its symptoms and to prevent disability in patients. This review is focused on therapeutic effects of some medicinal plants and their ingredients on PD. The findings presented in this review were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…e anti-inflammatory and antiallergic properties of quercetin on respiratory and food allergies were also shown [67,68]. Antiallergic [69], neuroprotective [70], antiinflammatory, and antioxidant activities [71] were shown for derivatives of A. cepa including flavonoids, organosulfur, and phenols. e polyphenol compounds present in onions showed stimulating effects on the immune system in the aging process [72,73], and some phenolics in onions showed antiplatelet properties [74].…”
Section: Traditional and Pharmacological Effectsmentioning
confidence: 92%
See 2 more Smart Citations
“…e anti-inflammatory and antiallergic properties of quercetin on respiratory and food allergies were also shown [67,68]. Antiallergic [69], neuroprotective [70], antiinflammatory, and antioxidant activities [71] were shown for derivatives of A. cepa including flavonoids, organosulfur, and phenols. e polyphenol compounds present in onions showed stimulating effects on the immune system in the aging process [72,73], and some phenolics in onions showed antiplatelet properties [74].…”
Section: Traditional and Pharmacological Effectsmentioning
confidence: 92%
“…The anti-inflammatory and antiallergic properties of quercetin on respiratory and food allergies were also shown [ 67 , 68 ]. Antiallergic [ 69 ], neuroprotective [ 70 ], anti-inflammatory, and antioxidant activities [ 71 ] were shown for derivatives of A. cepa including flavonoids, organosulfur, and phenols.…”
Section: Traditional and Pharmacological Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its compounds might mitigate neurodegeneration by lowering ROS levels in the brain, preventing nitric oxide (NO) accumulation and promoting the enhancement of α‐synuclein clearance. They also act on the inhibition of MAOs and the modulation of the content of DA (Amro, Teoh, Norzana, & Srijit, 2018; Khazdair, Kianmehr, & Anaeigoudari, 2021; Peterson, 2020).…”
Section: Phytotherapy For Neurodegenerative Dementiasmentioning
confidence: 99%
“…It is revealed that flavonoid, saponin, essential oil and carotenoid are the potential primary active components in CoL ( Machado et al, 2014 ). Thereinto, flavonoid has shown numerous health benefits, including the promising neuroprotective effect against PD ( Khazdair et al, 2021 ). Therefore, we hypothesized that the extract of CoL (hereafter referred as ECoL) may have potential activity for the prevention of PD.…”
Section: Introductionmentioning
confidence: 99%